2006
DOI: 10.1103/physrevb.74.041305
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field inversion asymmetry: Rashba and Stark effects for holes in resonant tunneling devices

Abstract: We report experimental evidence of excitonic spin-splitting, in addition to the conventional Zeeman effect, produced by a combination of the Rashba spin-orbit interaction, Stark shift and charge screening. The electric-field-induced modulation of the spin-splitting are studied during the charging and discharging processes of p-type GaAs/AlAs double barrier resonant tunneling diodes (RTD) under applied bias and magnetic field. The abrupt changes in the photoluminescence, with the applied bias, provide informati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…However, our experimental results must be attributed to the electric field-induced coupling of the hole spin degree of freedom, the Rashba spin orbit and Stark effects on the whole electronic structure. 15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our experimental results must be attributed to the electric field-induced coupling of the hole spin degree of freedom, the Rashba spin orbit and Stark effects on the whole electronic structure. 15 …”
Section: Resultsmentioning
confidence: 99%
“…10,11 Furthermore, resonant tunneling diodes (RTDs) are interesting devices for studying the physical properties of 2D systems due to the fact that their carrier density and the resulting parameters, such as the filling factor, can be varied by the applied bias voltage. [12][13][14][15][16][17][18][19][20][21] Several previous works have shown that 2DHG formed in the accumulation layer can inject spin-polarized holes in the quantum well (QW) region and make an important contribution to the spin polarization of carriers in resonant tunneling diodes. 21 In this paper, we have investigated the effect of the electric field and laser excitation intensity on the spin properties of 2DHGs formed at the accumulation layer next to the emitter barrier of a ptype GaAs/AlAs resonant tunneling diode.…”
Section: Introductionmentioning
confidence: 99%
“…The current I depends on the transmission probability and the electron supply function, 16,17 while the RTD voltage drop, V rtd , is mainly determined by the arrangement of accumulated electron and ionized donor densities. 18 Two electron densities, n ac and n i , are formed due …”
Section: Resultsmentioning
confidence: 99%
“…Resonant tunneling diodes (RTDs) have also been a research focus for many years [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Several works investigated their fundamental physical properties and possible potential applications in spintronics [8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Several works investigated their fundamental physical properties and possible potential applications in spintronics [8][9][10][11][12][13][14][15][16][17] . For example, it was shown that spin polarization of carriers in RTDs can be voltage and light dependent under magnetic field [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%